THE STUDY ON EFFECTIVE USAGE OF SOCIAL MEDIA MARKETING SERVICES IN HIGHER EDUCATIONAL INSTITUTIONS (Neo Scientific Peer Reviewed Journal, 2024)
The advent of social media has significantly transformed marketing strategies across various sectors, including higher education. This study investigates the effective use of social media marketing services in higher educational institutions (HEIs). By examining current practices, challenges, and opportunities, this research aims to provide a comprehensive understanding of how HEIs can leverage social media to enhance their marketing efforts, improve student engagement, and strengthen their institutional brand. Through a mixed-methods approach, including surveys, interviews, and case studies, the study identifies key factors that contribute to successful social media campaigns in higher education. The findings suggest that strategic planning, targeted content, and consistent engagement are crucial for maximizing the impact of social media marketing in HEIs. Additionally, the research highlights the importance of adapting to emerging trends and technologies to stay competitive in a rapidly evolving digital landscape.